Pengembangan LKPD Berbasis PBL-SSI Aktivitas Penambangan Pasir di Sungai Progo untuk Meningkatkan Literasi Sains - Puri, Putri Rose Amanda; Jumadi; Wiyatmo, Yusman (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
The purpose of this research is to produce a worksheet based on the PBL model with the SSI approach of sand mining activity in the Progo river, which is feasible, practical, and effective to improve the scientific literacy ability of high school students on vector material. This study used R&D with the ADDIE model. This research was conducted in April-May of the 2024/2025 school year at SMA N 1 Sewon, involving 32 class X students. This study employed both descriptive and inferential data analysis techniques. The descriptive analysis SBi, Aiken’s V, and N-Gain. Meanwhile, the inferential analysis involved ANOVA testing and effect size calculation. The results indicated that the worksheet was very feasible, practical, and effective in improving students’ scientific literacy with a gain value of 0,65 (moderate improvement) and a significance of 0,037. In addition, worksheet has a significant effect on improving students’ scientific literacy. The implication is that this PBL-SSI model-based worksheet can be developed for other physics materials and become a solution to the demands of 21st-century learning.